Dead in the frame - Spotswood, Stephen (Spotswood, Stephen. Pentecost and Parker mystery, 2025)
"The most dramatic installment yet in the Nero Award-winning Pentecost and Parker series, as Will scrambles to solve a shocking murder before Lillian takes the fall for the crime. NEW YORK CITY, 1947: Wealthy financier and ghoulish connoisseur of crime, Jessup Quincannon, is dead, and famed detective Lillian Pentecost is under arrest for his murder. Means, motive, and a mountain of evidence leave everyone believing she's guilty. Everyone, that is, except Willowjean "Will" Parker, who knows for a fact her boss is innocent. She just doesn't know if she can prove it. With Lillian locked away in the House of D-New York City's infamous women's prison-Will is left to root out the real killer. Was it a member of Quincannon's murder-obsessed Black Museum Club? Maybe it was his jilted lover? Or his beautiful, certainly-sociopathic bodyguard? And what about the mob hit-man who just happened to disappear after the shots were fired? With the city barreling toward the trial of the century, each day brings fresh headlines and hints of long-buried scandals from Lillian's past. Will is desperate to get her boss out from behind bars before her reputation is destroyed. Because the House of D is no kind place, especially for a woman with multiple sclerosis. Or one with so many enemies. Her health failing and targeted by someone who wants her dead, Lillian needs to survive long enough to take the stand. With time running out on both sides of the prison walls, Will and Lillian must wager everything to uncover who put their thumb on the scales and a bullet in Quincannon's head. Before Lady Justice brings her sword down, ending Pentecost and Parker's adventures once and for all"--